Analisis Dampak Kebijakan Publik Terhadap Aksesibilitas Layanan Mypertamina di SPBU Kecamatan Kawangkoan - Rebecca Christy Mowilos; Ismiati Essing; Yemima Otuluwa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research analyzes the implementation of fuel service digitization policy through MyPertamina application at Kawangkoan Subdistrict Service Station. Using a qualitative approach and case study method, the research collected data through in-depth interviews of 20 users, 4 gas station managers, and 2 related agency officials, as well as field observations. The findings of the study reveal that this policy has successfully increased transparencyof prices) and reduced queues but faces serious challenges in terms of accessibility. Many users experience difficulties due to low digital literacy, compounded by unstable internet infrastructure and lack of socialization. This research reinforces the digital divide theory and shows the mismatch between policy design and the real conditions of local communities. The implications of the research highlight the importance of a more inclusive policy approach, by recommending: (1) strengthening digital infrastructure, (2) targeted digital literacy programs, and (3) hybrid policy mechanisms that maintain conventional service options. The findings provide an important contribution to the formulation of digital-based public policies in semi-urban areas with similar characteristics